Edmund Cody Burnett papers - Burnett, Edmund Cody, 1864-1949.; Burnett, Edmund Cody, 1864-1949
Correspondence, memoranda, drafts of writings, speeches, notes, research material, financial and legal papers, and a project file from Burnett's work for the Carnegie Institution of Washington as editor of the Letters of Members of the Continental Congress, published from 1921 to 1936. The project file includes editorial instructions, research material, draft of introduction, speech, and transcriptions, photostats, and printer's copies of letters and documents. The collection also reflects Burnett's interest in and writings on Tennessee local history, Burnett family history and genealogy, nature, and farming and agrarian issues, especially in relation to his family farm in Tennessee, the environmental impact of the Tennessee Valley Authority projects, and economic effects of New Deal government farm programs. Includes original and edited Civil War correspondence of the Burnett, Cody, Lightfoot, and McGarity families. Also includes Burnett's translation of ciphers used by the Lee family of Virginia. Burnett's correspondents include Arthur Deerin Call, R.D.W. Connor, Max Farrand, Charles Earle Funk, J. Franklin Jameson, Waldo Gifford Leland, Dumas Malone, and Charles Oscar Paullin.
In part, photostats.
Library of Congress General Collections.
Historian, editor, and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Cipher material concerning the Lee family of Virginia was transferred from the Ethel Armes Collection of Lee Family Papers in the Manuscript Division to these papers in 1998.
Keywords: Call, Arthur Deerin, -- 1869-1941 -- Correspondence; Connor, R. D. W. -- 1878-1950 -- Correspondence; Farrand, Max, -- 1869-1945 -- Correspondence; Funk, Charles Earle, -- 1881-1957 -- Correspondence; Jameson, J. Franklin -- 1859-1937 -- Correspondence; Leland, Waldo Gifford, -- 1879-1966 -- Correspondence; Malone, Dumas, -- 1892-1986 -- Correspondence; Paullin, Charles Oscar, -- 1868 or 1869-1944 -- Correspondence; Burnett family; Cody family; Lee family; Lightfoot family; McGarity family; United States. -- Continental Congress; Carnegie Institution of Washington; Tennessee Valley Authority; Agriculture -- Economic aspects; Agriculture -- Tennessee; Agriculture and state; Ciphers -- Virginia; Genealogy -- Tennessee; Nature; New Deal, 1933-1939.; Water resources development -- Tennessee Valley; Tennessee -- History, Local; Tennessee -- Social life and customs; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- Revolution, 1775-1783.; United States -- History -- Confederation, 1783-1789.; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- To 1775.; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1789.; Editors; Educators; Historians